Evaluation of the thoracic epidural spread after caudal thoracic contrast medium injections in cat cadavers - Franci, Paolo; Santoro, Francesco; Landi, Alessandra; Manassero, Luca; Lardone, Elena (Frontiers in Veterinary Science, 2025)
BackgroundThoracic epidural anesthesia (TEA) offers significant analgesic benefits in humans undergoing major surgery. However, this technique remains underexplored in feline medicine due to anatomical challenges and limited data on epidural drug distribution.ObjectiveTo assess the feasibility of a paramedian approach and characterize the epidural spread of 0.3 mL/kg of contrast medium administered in three consecutive aliquots of 0.1 mL/kg at the 12th–13th thoracic vertebrae (T12–T13) level in cat cadavers.MethodsSeven refrigerated cat cadavers underwent three consecutive thoracic epidural administrations of 0.1 mL/kg of iodinated contrast medium (total dose injected 0.3 mL/kg) administered at the T12–T13 interspace using a 25 G, 25 mm Quincke needle via a paramedian technique. Computed tomography was used to evaluate longitudinal and circumferential distribution 5 min after each dose.ResultsEpidural spread increased significantly with incremental dosing (longitudinal τ = 0.63, p < 0.001; circumferential τ = 0.58, p = 0.001). The percentage of longitudinal and circumferential median spread increase, when compared with the previous dose, was, respectively, 46 and 45% for D2, and 17 and 70% for D3. The initial injection preferentially spread cranially (p < 0.05), however, cervical segments were reached in only one case, while the sacral segments were never reached. No significant effect of gravity on circumferential spread was observed.ConclusionThis study demonstrates the feasibility of TEA via a paramedian approach in cats and provides novel insight into epidural fluid distribution patterns.